Preliminary Study on the Development of Infographic-Based Islamic Education Teaching Materials to Improve Soft Skills for High School Students in Surakarta - Pramesti Wulandari; Asrowi Asrowi; Djono Djono (Jurnal Pendidikan Agama Islam, 2022)
Purpose – This research aims to conduct an initial assessment of students' attitudes in high school, with a focus on Islamic education, which is one of the benchmarks in soft skills development activities.